Solifenacin versus posterior tibial nerve stimulation for overactive bladder in patients with multiple sclerosis - Majdinasab, Nastaran; Orakifar, Neda; Kouti, Leila; Shamsaei, Gholamreza; Seyedtabib, Maryam; Jafari, Mohammad (Frontiers in Neuroscience, 2023)
Introduction Overactive bladder (OAB) is one of the most common complications in patients with multiple sclerosis (MS). Choosing the effective treatment is very important in improving their quality of life (QOL). Therefore, the aim of this study was to compare solifenacin (SS) and posterior tibial nerve stimulation (PTNS) treatment effects in the MS Patients with OAB. Materials and methods In total, 70 MS patients suffering from OAB enrolled in this clinical trial study. Patients with a score of at least 3 according to the OAB questionnaire were randomly divided into two groups (35 patients in each group). In one group, patients received SS (5 mg daily for 4 weeks and 10 mg/day for another 8 weeks) and in a second group, patients were treated by PTNS (12 weekly session, 30 min). Results The mean (SD) age of patients participating in this study was 39.82 (9.088) and 42.41 (9.175) years for the SS group and the PTNS group, respectively. Patients in both groups showed statistically significant improvements in urinary incontinence, micturition, and daytime frequency (p < 0.001). Patients in the SS group had a better response for urinary incontinence after 12 weeks compared to the PTNS group. Also, patients in the SS group reported higher satisfaction and less daytime frequency compared to the PTNS group. Conclusion SS and PTNS were effective for improving the OAB symptoms in patients with MS. However, patients demonstrated a better experience with SS in terms of daytime frequency, urinary incontinence, and treatment satisfaction rate.